2013
DOI: 10.1186/gm406
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA paraffin-based studies in osteosarcoma reveal reproducible independent prognostic profiles at 14q32

Abstract: BackgroundAlthough microRNAs (miRNAs) are implicated in osteosarcoma biology and chemoresponse, miRNA prognostic models are still needed, particularly because prognosis is imperfectly correlated with chemoresponse. Formalin-fixed, paraffin-embedded tissue is a necessary resource for biomarker studies in this malignancy with limited frozen tissue availability.MethodsWe performed miRNA and mRNA microarray formalin-fixed, paraffin-embedded assays in 65 osteosarcoma biopsy and 26 paired post-chemotherapy resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 40 publications
4
100
0
2
Order By: Relevance
“…A locus at 14q32 associated with miR-382, miR-134 and miR-544 has demonstrated an inverse correlation between aggressive tumor behavior and residual expression of microRNAs. [9, 10] DNA methylation analysis may reveal patterns with prognostic significance. [11] Further evaluation and prospective validation of these markers in future studies will establish their role in prognostication of tumor response and survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A locus at 14q32 associated with miR-382, miR-134 and miR-544 has demonstrated an inverse correlation between aggressive tumor behavior and residual expression of microRNAs. [9, 10] DNA methylation analysis may reveal patterns with prognostic significance. [11] Further evaluation and prospective validation of these markers in future studies will establish their role in prognostication of tumor response and survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that miR-433 was upregulated in osteosarcoma tissues compared with the adjacent normal tissues, and inhibited osteosarcoma apoptosis. The present data, along with an analysis of a published dataset (27), showed that miR-433 was overexpressed in osteosarcoma tissues and cell lines. In combi nation with previous reports revealing the roles of miR-433 in various other types of cancer, including ovarian and gastric cancer (28,29), the present study further confirmed that miR-433 functions as an oncomiR in osteosarcoma.…”
Section: Discussionmentioning
confidence: 98%
“…Beste adibide bat 14q32 gune kromosomikoan dagoen miRNA-klusterra da, OSaren progresioarekin eta pronostikoarekin erlazionatu dena [52].…”
Section: Osteosarkoma Pediatrikoarekiko Suszeptibilitatean Inplikatutunclassified